Eruption Interval Monitoring at Strokkur Geyser, Iceland. Issue 1 (17th January 2020) - Eibl, Eva P. S.; Hainzl, Sebastian; Vesely, Nele I. K.; Walter, Thomas R.; Jousset, Philippe; Hersir, Gylfi Páll; Dahm, Torsten
Abstract: Geysers are hot springs whose frequency of water eruptions remain poorly understood. We set up a local broadband seismic network for 1 year at Strokkur geyser, Iceland, and developed an unprecedented catalog of 73, 466 eruptions. We detected 50, 135 single eruptions but find that the geyser is also characterized by sets of up to six eruptions in quick succession. The number of single to sextuple eruptions exponentially decreased, while the mean waiting time after an eruption linearly increased (3.7 to 16.4 min). While secondary eruptions within double to sextuple eruptions have a smaller mean seismic amplitude, the amplitude of the first eruption is comparable for all eruption types. We statistically model the eruption frequency assuming discharges proportional to the eruption multiplicity and a constant probability for subsequent events within a multituple eruption. The waiting time after an eruption is predictable but not the type or amplitude of the next one. Plain Language Summary: Geysers are springs that often erupt in hot water fountains. They erupt more often than volcanoes but are quite similar. Nevertheless, it is poorly understood how often volcanoes and also geysers erupt. We created a list of 73, 466 eruption times of Strokkur geyser, Iceland, from 1 year of seismic data. The geyser erupted one to six times in quick succession. We found 50, 135 single eruptions but only 1 sextuple eruption, while the mean waiting time increased from 3.7 min after single eruptions to 16.4 min after sextuple eruptions. Mean amplitudes of each eruption type were higher for single eruptions, but all first eruptions in a succession were similar in height. Assuming a constant heat inflow at depth, we can predict the waiting time after an eruption but not the type or amplitude of the next one. Key Points: We create a catalog of 73, 466 eruptions of Strokkur geyser, Iceland, from a 1 year seismic data set Single to sextuple eruptions are followed by a mean waiting time of 3.7 to 16.4 min, respectively Waiting time after an eruption can be predicted, while future eruption type or amplitude cannot